Analisis Strategi Pencegahan Perilaku Bully Verbal di Sekolah Dasar Negeri 1 Nanga Pinoh - Eliska Monalika; Mastiah; Eko Rudiansyah (STKIP Melawi, 2026)
Abstract: This study aimed to describe strategies for preventing verbal bullying behavior at SDN 1 Nanga Pinoh. The research employed a qualitative method with a descriptive approach and used a case study design. The main subject of the study was the third-grade classroom teacher, while the supporting subjects were third-grade students and the school principal. The object of the study was strategies for preventing verbal bullying behavior in an elementary school. Data were collected through interviews and observations using interview guides and observation sheets as research instruments. The validity of the data was ensured through technique triangulation and source triangulation. The results showed that the strategies for preventing verbal bullying at SDN 1 Nanga Pinoh consisted of several efforts. Preventive efforts included early detection of bullying behavior, providing education, and creating a positive school environment by establishing strict anti-bullying rules. Promotive efforts were carried out by providing good role models and teaching students how to stand up against bullying. Repressive efforts involved imposing sanctions on perpetrators and implementing disciplinary actions. Curative efforts included providing support for victims and conducting mediation between victims and perpetrators. In addition, efforts to increase self-confidence were made by helping victims of verbal bullying improve their self-esteem and their ability to defend themselves. In conclusion, the prevention of verbal bullying behavior at SDN 1 Nanga Pinoh is implemented through a combination of preventive, promotive, repressive, and curative strategies. Keywords: Teacher Strategy, Prevention, Verbal Bully. Abstrak: Tujuan penelitian mendeskripsikan strategi pencegahan perilaku bully vebal di SDN 1 Nanga Pinoh. Penelitian menggunakan metode kualitatif dengan pendekatan deskriptif. Jenis penelitian studi kasus. Subjek utama penelitian guru kelas III. Subjek pendukung siswa kelas III dan kepala sekolah. Objek penelitian strategi pencegahan perilaku bully verbal di Sekolah Dasar. Teknik pengumpulan data menggunakan wawancara dan obsevasi. Instrumen penelitian menggunakan lembar wawancara dan lembar observasi. Pengecekan keabsahan data menggunakan triangulasi teknik dan sumber. Hasil penelitian diketahui bahwa strategi dalam mencegah perilaku bullying vebal di SDN 1 Nanga Pinoh dengan upaya preventif seperti mendeteksi tindakan bullying sejak dini, memberikan edukasi dan membangun lingkungan sekolah yang positif dengan membuat peraturan yang tegas tentang bullying. Upaya promotif dengan memberikan teladan atau contoh yang baik dalam mengatasi bullying mengajarkan siswa untuk melawan bullying. Upaya represif yaitu melibatkan sanksi bagi pelaku dan tindakan disiplin. Upaya kuratif dengan memberikan dukungan pada korban, mediasi bagi korban dan pelaku. Peningkatan kepercayaan diri dengan membantu siswa yang menjadi korban bullying verbal untuk meningkatkan kepercayaan diri dan kemampuannya untuk membela diri. Kesimpulan penelitian stategi pencegahan perilaku bullying verbal di SDN 1 Nanga Pinoh dengan berbagai upaya preventif, represif, dan kuratif. Kata Kunci: Strategi Guru, Pencegahan, Bully Verbal.